A review on clinical, pathological characteristics and drug designing for COVID-19. Issue 1 (1st January 2021) - Ashraf, Muhammad Usama; Sharif, Sundas; Ahmad, Muhammad Usman; Zahid, Muhammad Nauman; Mukhtar, Hamid
Abstract: In late 2019, a novel strain of coronavirus (2019-nCoV) named as severe respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in Wuhan, a city in China, through some zoonotic reservoir, most probably a bat, and spread throughout the world. There have been around 22, 213, 869 reported cases of COVID-19 and almost 781, 677 deaths worldwide according to the data updated by World Health Organization till 20 August 2020. It transmitted via droplets from an infected person to a healthy person in a very short duration of time. After the completion of the incubation period, which ranges from 2 to 14 days, the person experiences pneumonia-like symptoms such as fever, sore throat, cough, breathlessness, malaise, fatigue, and multi-organ dysfunction, etc. The main receptor of SARS-CoV-2 is angiotensin-converting enzyme 2 which binds with the spike (S) protein of the virus and helps it in attachment and entry to the host cells. COVID-19 is diagnosed by molecular testing of respiratory secretions and CT scan analysis. Because of the absence of any approved treatment options for COVID-19, a number of research studies are being carried out to find out any combination of already approved drugs or new lead compounds using in silico docking and screening strategies.